Integrative pan-resistome and transcriptomic characterization reveals differential gene expression signatures in carbapenem-resistant Acinetobacter baumannii: Insights into efflux pump regulation and therapeutic targeting strategies - Mohanraj Gopikrishnan; George Priya Doss C (PLoS ONE, 2026)
Acinetobacter baumannii is a significant, multidrug-resistant pathogen that is increasingly recognized as an agent associated with hospital infections. Its increasing resistance to carbapenems and other necessary antibiotics poses a serious threat to public health worldwide. The present study provides an integrative analysis of the pan-resistome and transcriptomic landscape of carbapenem-resistant A. baumannii (CRAB) under sub-minimum inhibitory concentrations (sub-MICs) of clinically relevant antibiotics, i.e., ciprofloxacin, amikacin sulfate, meropenem, and polymyxin B. A focused investigation was conducted into the transcriptional modulation of efflux transport systems and cellular stress-response mechanisms. To identify differentially expressed genes (DEGs) among the CRAB strains, parallel comparative RNA-Seq analysis with already available public datasets was undertaken. Concurrently, high-throughput virtual screening against the comprehensive marine natural product database (CMNPD) was done to identify inhibitors for MacB, a major ABC-type efflux transporter. Binding stability and interaction profiles of lead compounds were assessed via molecular dynamics simulations of 1000 ns. Transcriptomic profiling consistently showed increased levels of MacA-MacB efflux components, RcnB an intracellular stress-response protein LolA an outer membrane chaperone and surface antigen protein 1, especially under polymyxin B exposure. CMNPD27284 is the best candidate, having a strong binding affinity and stable interaction networks with critical MacB residues (−7.20 kcal/mol). These results highlight that efflux-mediated resistance and stress adaptation are crucial factors in CRAB, and they also indicate CMNPD27284 as a potential candidate for marine-derived scaffolding in developing drugs targeting the efflux pump.